A review on global fuel economy standards, labels and technologies in the transportation sector - Atabani, A.E.; Badruddin, Irfan Anjum; Mekhilef, Saad; Silitonga, A.S. (Elsevier, 2011)
Globally, the transportation sector is the second largest energy consuming sector after the industrial sector and accounts for 30% of the world's total delivered energy. In 2008 the transportation sector accounted for about 22% of total world CO2 emissions. It is believed that this sector is currently responsible for nearly 60% of world oil demand. Within this sector, road vehicles dominate oil consumption and represents 81% of total transportation energy demand. The purpose of this paper is to highlight the possible opportunities to improve fuel economy and thus reduce global oil consumption and greenhouse gases. There are three measures that have been reviewed; passenger vehicle fuel economy and greenhouse gas emission standards, fuel economy labels and improvement in vehicle fuel efficiency by advanced technologies. Fuel economy and greenhouse gas emission standards have proven to be one of the most effective tools in improving fuel economy. Japan and Europe lead the world with the most stringent passenger vehicle fuel economy standards. Labeling is another measure that could play an important role in consumers' vehicle purchasing decisions between similar vehicles. Labeling accompanied by standards of an appropriate type and level of stringency may yield synergistic results. In this review, several examples of fuel economy labels around the world have been presented such as in USA, United Kingdom, Canada, China and Australia. Finally, advanced technologies have been discussed. There are many technical opportunities to improve fuel efficiency and economy of motor vehicles. In this review, the possibilities of reducing vehicle power requirement, advanced engine and transmission technology and alternative power plants have been reviewed. It has been found that fuel economy standards, labels and technologies offer a massive potential of energy saving that can be achieved in this sector and thus the authors promoted adopting these measures in the transportation sector. (C) 2011 Elsevier Ltd. All rights reserved.